1985
DOI: 10.1097/00012272-198504000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive behavior in college-age males related to Fishbein model

Abstract: Fishbein's Belief-Attitude-Intention-Behavior model states that behavior is predicted on intention, intention is predicated on attitudes, and attitudes are predicated on beliefs. Path analysis was used to test the model with respect to the contraceptive behaviors of 54 college males. In spite of the heterogeneity of the sample, the data supported the model, suggesting that nursing interventions may need to be directed toward beliefs rather than behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In the area of condom use, several studies have found that the TRA accounts for 30-40% of variance in condom use intentions and 20-30% of variance in reported condom use (Ewald & Roberts, 1985;Fisher, 1984;McCarty, 198 1). Both the normative and expectancy value components of the TRA were significant predictors of condom use intention in these studies.…”
Section: Theory Of Reasoned Actionmentioning
confidence: 99%
“…In the area of condom use, several studies have found that the TRA accounts for 30-40% of variance in condom use intentions and 20-30% of variance in reported condom use (Ewald & Roberts, 1985;Fisher, 1984;McCarty, 198 1). Both the normative and expectancy value components of the TRA were significant predictors of condom use intention in these studies.…”
Section: Theory Of Reasoned Actionmentioning
confidence: 99%
“…Studies based conceptually on the TRA and the TPB have provided evidence of positive associations between beliefs and attitudes about the outcomes of using birth control pills, condoms, and various contraceptives, and intention to use, and/or use of birth control pills; [19][20][21] and intention to use and/or use of condoms. 9,19,[22][23][24][25][26][27] Similarly, there is some evidence, in studies using the TRA and the TPB, for the relationship between subjective norms and intention to use and/or use of condoms; [22][23][24][25][26][27][28][29][30][31] and intention to use and/or use of oral contraceptives. [19][20][21] Although studied to a lesser extent, perceived behavioural control has been found to be associated with intention to use condoms.…”
mentioning
confidence: 99%
“…Attitudes of young men and women toward condom use vary widely (Finkel & Finkel, 1976). Some males have indicated their intention to use condoms (Ewald & Roberts, 1985), while other young males and females believe condoms interfere with sexual pleasure (Dryfoos, 1985;Clark, Jabin, & Hardy, 1984). In the hope that mass education increases the use of condoms to prevent HIV transmission and other sexually transmitted diseases (STDs), health educators have made large-scale efforts to provide knowledge to particular target groups (McKusick, Horstman, & Coates, 1985;Valdiserri, Lyter, Kingsley, Leviton, Schofield, Huggins, Monton, & Runaldo, 1987;Townsend, Diaz De May, Sepulveda, Santos de Garsal, & Rosenhouse, 1987).…”
mentioning
confidence: 99%